A model of persistent Salmonella infection: Salmonella pullorum modulates the immune response of the chicken from a Th17 towards a Th2-type response - Tnag, Ying; Foster, Neil; Jones, Michael; Barrow, Paul (ASM, 2018)
Salmonella enterica infection affects a wide range of animals and human and a small number of serovars cause typhoid-like infections, one characteristic of which is persistent infection in convalescents. The avian specific serovar S Pullorum produces systemic disease in young chickens which is followed by a carrier state in convalescent birds leading to infection of the ovary at sexual maturity and vertical transmission. However, the immunological basis of the persistent infection remains unclear. S. Enteritidis is taxonomically closely related but does not show this characteristic. Differences in the immune responses between S. Pullorum and S. Enteritidis were compared using Salmonella-infected chicken monocyte-derived macrophages (chMDMs) and CD4+ T lymphocytes which had been co-cultured with infected chMDMs or chicken splenocytes in vitro and also in 2-day-old chickens in vivo In comparison with S. Enteritidis, S. Pullorum-infected chMDMs showed reduced mRNA expression of IL-12α and IL-18 and stimulated proliferation of Th2 lymphocytes with reduced expression of IFN-γ and IL-17 and increased expression of IL-4 and IL-13 There was little evidence of clonal anergy or immune suppression induced by S. Pullorum in vitroS. Pullorum also increased levels of expression of IL-4 and lower levels of IFN-γ in the spleen and cecal tonsil of infected birds. This suggests that S. Pullorum is able to modulate host immunity from a dominant IFN-γ-producing Th17 response towards a Th2 response, which may promote the persistent infection in chickens. S. Pullorum in chickens is presented as a good model of the typhoid group to study persistent infection.